Cost-Benefit Analysis and Emission Reduction of Energy Efficient Lighting at the Universiti Tenaga Nasional - Ganandran, G. S. B. (Hindawi Publishing Corporation, 2014)
This paper reports the result of an investigation on the potential energy saving of the lighting systems at selected buildings of the Universiti Tenaga Nasional. The scope of this project includes evaluation of the lighting system in the Library, Admin Building, College of Engineering, College of Information Technology, Apartments, and COE Food court of the university. The main objectives of this project are to design the proper retrofit scenario and to calculate the potential electricity saving, the payback period, and the potential environmental benefits. In this survey the policy for retrofitting the old lighting system with the new energy saving LEDs starts with 10% for the first year and continues constantly for 10 years until all the lighting systems have been replaced. The result of the life cycle analysis reveals that after four years, the selected buildings will bring profit for the investment.